2016
DOI: 10.1038/srep21667
|View full text |Cite|
|
Sign up to set email alerts
|

Non-ionizing radiofrequency electromagnetic waves traversing the head can be used to detect cerebrovascular autoregulation responses

Abstract: Monitoring changes in non-ionizing radiofrequency electromagnetic waves as they traverse the brain can detect the effects of stimuli employed in cerebrovascular autoregulation (CVA) tests on the brain, without contact and in real time. CVA is a physiological phenomenon of importance to health, used for diagnosis of a number of diseases of the brain with a vascular component. The technology described here is being developed for use in diagnosis of injuries and diseases of the brain in rural and economically und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…MIPS data were obtained from the phase of S21 at its characteristic frequency (53.7 MHz), where the transmission coefficient reach its maximum. The selection method of characteristic frequency comes from previous researches (Pan et al, 2015;Li et al, 2017a;Li et al, 2017b;Li et al, 2017c;Oziel et al, 2016). Physical and subsequent animal experiments were both carried out under those parameter settings.…”
Section: Physical Experimentsmentioning
confidence: 99%
“…MIPS data were obtained from the phase of S21 at its characteristic frequency (53.7 MHz), where the transmission coefficient reach its maximum. The selection method of characteristic frequency comes from previous researches (Pan et al, 2015;Li et al, 2017a;Li et al, 2017b;Li et al, 2017c;Oziel et al, 2016). Physical and subsequent animal experiments were both carried out under those parameter settings.…”
Section: Physical Experimentsmentioning
confidence: 99%
“…spectroscopy could be used physically to separate electromagnetic waves of various frequencies [13,14]. erefore, it generates a spectrum which shows the constituents' frequencies [15,16].…”
Section: Spectroscopy a Characterization Technique Known Asmentioning
confidence: 99%
“…In a clinical study with 248 subjects, VIPS has shown that it can detect a severe stroke in seconds with a 92% accuracy (Kellner et al, 2018) and has been chosen as one of the top ten medical innovations for 2019 (Cleveland Clinic, 2019). VIPS has received FDA and CE approval and is used clinically to detect brain hemorrhages (González et al,2014), cerebrovascular autoregulation monitoring (Oziel et al, 2016), or to detect fluid shifts in the brain during dialysis (Rao, 2018). There are many other uses of RF/MW measurements for diagnostics in medicine.…”
Section: Introductionmentioning
confidence: 99%